Sustaining local livelihoods through carbon sequestration activities: a search for practical and strategic approach - Murdiyarso, Daniel (Center for International Forestry Research, 2005)
In many parts of the developing world carbon sequestration projects have been implemented in association with community development. This is a practical way to demonstrate environmental as well as social benefits of the projects. To some extent the projects are in line with the dual objectives of the Kyoto Protocol’s Clean Development Mechanism (CDM). Knowing the immaturity of CDM market and the dynamics of the negotiations in the Conferences of Parties (COPs) to the United Nations Framework Convention on Climate Change (UNFCCC), it is timely to explore strategic and long-term approaches. This paper attempts to synthesize the lessons learned from Mexico, Colombia, Costa Rica, Philippines, Indonesia, and Timor Leste presented and discussed in the workshop to mark the entry into force of the Kyoto Protocol. Most of the projects do not necessarily comply with the strict rules of CDM partly due to the fact that the current agreement only allows afforestation and reforestation activities. Conservation of carbon storage (e.g. in peatlands) is not eligible for funding under the existing rules. Strategic approaches, such as inclusion of deforestation avoidance in the next round of negotiations and subsequent commitment period, were critically reviewed. A number of loopholes that require scientifically sound justification were identified. In addition, issues related to methodologies to determine the baseline, monitor additionality, leakage and permanence remain challenging. It is generally demonstrated that local participation is very strong in all of the projects examined. It was learned that large-scale plantation projects offer few benefits for the community, whereas small-scale projects that allow the community to participate offer the possibility to earn carbon credits as well as socio-economic and cultural benefits. However, many of these projects are so small in size that they generate high transaction costs. Otherwise the projects could demonstrate financial additionality from the point of view of the hosts. It was strongly suggested that in order to sustain livelihoods the projects have to be recognized by and linked with donor and policy communities. In addition, engagement of the private sector has to be further explored.